RHYTHMANALYSIS: MEMAHAMI RITUS SEBAGAI PLACEMAKING TEMPORAL - Michael, George; Ekomadyo, Agus Suharjono (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2023)
Rites is a part of Indonesian culture that involves human, place, and time. These three elements are closely related to placemaking theory which aims to improve the quality of a place. However, the current theory and categorization of placemaking have not been able to accommodate rites as part of placemaking. This article will explore the relationship between rite and placemaking using Wyckoff's (2014) key elements of Quality Places. Then, the results are further elaborated with rhythmanalysis theory by Lefebvre (2004). The findings of this study it that rites are indeed part of placemaking. Using rhythmanalysis, we can infer that rite has an element of depth in the temporal dimension, which is rhythm, that is not shared by other types of placemaking. Therefore, rites should be categorized as a different type of placemaking such as temporal placemaking.